Inclusión de la igualdad en la hipótesis nula (2010)
A question the researchers get with some frequency is about the possibility of excluding the equal sign from the null hypothesis to include it into the alternative. They ﬁnd this convenient from teoretical or practical viewpoints. Some deﬁnitions given in the litterature allow this and the aim of this paper is to illustrate some errors in the statistical procedures as a consequence of doing so.